Green Purchasing Dalam Pengadaan Barang Kitchen di Hotel Aloft Bali Seminyak: Implementasi dan Kendala Menuju Hospitaliti Berkelanjutan - Kadek Rizki Ariatpernawan; Dewa Ayu Diyah Sri Widari; I Gusti Agung Rendra Wijaya (Jurnal Mosaik Hospitaliti, 2026)
This research focuses on the implementation of green purchasing as one of the efforts to support environmental preservation. This study aims to examine the implementation of green purchasing in the procurement of kitchen goods at Aloft Bali Seminyak Hotel and the inhibiting factors in its implementation. The research uses a qualitative descriptive approach with stages of data reduction, data presentation, and conclusion drawing. Data was collected through observation, interviews, and documentation studies. The technique for selecting informants used purposive sampling techniques involving key informants, namely the purchasing supervisor, sous chef, and receiving personnel. The findings indicate that the kitchen procurement process is systematic, but the green purchasing implementation is still low with a score of 43.9%. The main barriers include the use of single-use plastics by vendors, urgent purchases, and the lack of environmental audits for suppliers. Recommendations include establishing Green Purchasing SOPs, staff training, and collaboration with environmentally certified vendors.